Daya terima, Kandungan Kalori dan Kadar Beta Karoten Snack Bar Substitusi Cucurbita Moschata (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
Undernutrition is a nutritional problem that is susceptible to be experienced by children aged under five to school-age children. Efforts can be made to minimize malnutrition in children by giving additional food in the form of snacks made from pumpkins. The purpose of this study is to determine the acceptability (color, aroma, texture, taste), calorie content, and beta carotene snack bar substitution of Cucurbita moschata. This type of research is descriptive. The results showed that the receptivity of color as much as 61.5% of panelists said they like 55.4% of panelists like the aroma of snack bars. Receptivity texture as much as 63.1% panelists expressed very like and 81.5% panelists like the taste of pumpkin substitution snack bar. The nutritional content of the Cucurbita moschata snack contains calories of 359.65 kcal/100gr and beta carotene of 18.60 Âµg/ 100gr. Snack bar Cucurbita moschata is acceptable among school children but the nutritional value in this case the protein contained in the pumpkin snack bar (Cucurbita moschata) is still lacking, so it is advisable to modify the snack bar ingredients in adding and increasing the nutritional content under the nutritional needs of school children.